KAJIAN TENTANG APLIKASI SISTEM INFORMASI DAN PENGOLAHAN NILAI BERBASIS WEB DAN ANDROID PADA SD BUNDA MULIA - Jennifer Natashia (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Development of information technology affects human life, one of which is education. Every half term and increase in class, students will receive report cards so that teachers have to calculate the average value of each student subjects. Therefore, this application is made to petrify calculate the average value and help parents find out information about the activities of students in the school. The final value is obtained by first calculating the average task and quiz, then summing this average with UTS and UAS. After getting the results of that amount then the result is divided by 4.